Impact of periodontal knowledge and attitude on the status of the periodontium: A profile on West Godavari district, Andhra Pradesh, India - Penmetsa, Gautami Subhadra (J Indian Soc Periodontol, 2019)
BACKGROUND: Although regular patient education regarding the periodontal health/disease is advocated as a means of improving oral health, impregnable associations of periodontal knowledge and attitude with periodontal status have not been demonstrated. MATERIALS AND METHODS: In a cross-sectional study conducted, 2400 participants were surveyed using a specially designed pretested pro forma to evaluate the knowledge and attitude concerning periodontal health and disease. The oral exanimation included recording of oral hygiene index, gingival index (GI), community periodontal index (CPI), and loss of attachment. Ethical clearance was obtained from the institutional review board. The data were analyzed using IBM SPSS version 21.0. RESULTS: The mean age of the study population was 41.6 ± 9.5 years. The greater portion of individuals had high knowledge score (55.9%) and negative attitude (68.4%) toward periodontal health/disease. The mean oral hygiene index scores and GI scores were higher among individuals with high knowledge score and with negative attitude, and the differences were statistically significant among the groups. There was no difference in the mean plaque scores among individuals with different knowledge scores, but a higher score for individuals with negative attitude (1.24 ± 0.87) was evident. The proportion of individuals with healthy periodontium (score 0 for CPI and loss of attachment) had low knowledge score (54.3%); however, a positive attitude was elicited in 51.9% of the population. CONCLUSION: High knowledge score and negative attitude were related to periodontal status in West Godavari. Therefore, it can be emphasized that the presence of a positive attitude plays a key role in achieving better periodontal status.